Classification of Giardia lamblia Groups and Entamoeba histolytica-Entamoeba dispar Complex Using Molecular Diagnostic Technique (PCR) in Patients from Mosul - Mohammed AL-Ismaeeli, Amer Saadi (Journal of Neonatal Surgery, 2025)
Background: Giardia lamblia, Entamoeba histolytica, and Cryptosporidium are among the most common parasitic protozoa causing diarrheal diseases worldwide, and traditionally, the diagnosis of these infections has relied on the microscopic examination of stool samples, considered the "gold standard," also recent advancements in diagnostic techniques, like polymerase chain reaction (PCR), enzyme-linked immunosorbent assay (ELISA) and direct fluorescent-antibody tests, have provided more accurate and sensitive methods for detection. Objectives: This study aims to classify Giardia lamblia and the Entamoeba histolytica–Entamoeba dispar complex using a molecular diagnostic technique (PCR) among patients in Mosul, and the goal is to enhance diagnostic accuracy and efficiency in detecting these parasitic infections, particularly in regions where they are prevalent. Materials and Methods: A multiplex real-time PCR assay was developed for the simultaneous detection of Giardia lamblia, Entamoeba histolytica, and Cryptosporidium parvum in stool samples, and the assay includes an internal control to ensure PCR efficiency and identify potential inhibition. The assay was validated using species-specific DNA controls and well-characterized stool samples. Results: The multiplex PCR assay demonstrated 100% sensitivity and specificity when validated on species-specific DNA controls and stool samples, and this method provided accurate, reliable results in detecting the three targeted parasitic protozoa. Conclusion: This study's multiplex real-time PCR assay offers a highly accurate and efficient diagnostic tool for identifying Giardia lamblia, Entamoeba histolytica, and Cryptosporidium parvum infections in stool samples. Implementing this technique in diagnostic laboratories would improve patient care, enhance infection control measures, and contribute to the timely identification of these parasitic infections, particularly in regions like Mosul